A Context Aware Framework for User Centered Services - Hoh, Simon; Devaraju, Anusuriya; Wong, Chin Chin (2008)
In this paper, we introduce a context aware middleware framework that has been developed over the years to serve as an enabler for user centered services. Firstly, we will discuss about a sensory API mechanism developed to allow an abstraction of sensing elements to report information in a structured manner. We will then proceed to discuss how this sensed information is represented in an ontology, replicating a virtual model of the environment. This will facilitate reasoning capabilities, where entities that are inter-related can be resolved and used by the service. And finally we will describe how context specific to a user-centered service could be subscribed from the middleware. The context, once subscribed, will enable actions to be fired off when the particular context is met. The three core components when put together, will allow for services to react more specific to the users needs, based on the user’s ever changing context.